Pengaruh Ketidakpastian Globalisasi Keuangan dan Investasi Asing Langsung Terhadap Pertumbuhan Ekonomi dengan Pendekatan Akuntansi Arus Dana di Indonesia Tahun 2019-2022 - Dewi Ayu Wulandari; Rida Perwita Sari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Economic growth is an important indicator that reflects changes in a country's economic conditions toward a better state. Using a cash flow accounting approach, this study examines the effect of uncertainty in financial globalization and foreign direct investment on economic growth in Indonesia from 2019 to 2022. Indonesia's economic growth has fluctuated significantly during the COVID-19 pandemic, with a sharp decline in 2020 and recovery in 2021 and 2022. Global uncertainty and international conflicts, such as the Russia-Ukraine war, have also affected the global and domestic economies. Partial Least Square (PLS) analysis techniques and secondary time series data are used in this study’s quantitative methodology. The findings indicate that while foreign direct investment has a positive and considerable impact on economic growth, financial globalization uncertainty has no discernible impact on Indonesia’s economic growth. These result highlight the role that foreign investment plays in stimulating economic growth as well as the necessity of enacting laws that promote an environment that is favorable to investment. The cash flow accounting method offers a more thorough view of how foreign direct investment affects the domestic economy.